Self-Leadership : The Definitive Guide to Personal Excellence - Neck, Christopher P. (SAGE Publications, Inc. (US), 2024)
Written by the scholars who first developed the theory of self-leadership, Self-Leadership: The Definitive Guide to Personal Excellence 3e offers powerful yet practical advice for leading yourself to personal excellence.